Lateral loading performance of the joint between a precast concrete girder and a steel pier. (1st November 2019) - Lee, Heeyoung; Min, Junki; Cho, Sanghyun; Chung, Wonseok
Highlight: A new bridge system is proposed to minimize the amount of construction on site using precast structures. Full-scale connection specimens were fabricated and tested using a lateral load. A finite element model was also proposed and verified against experimental results. The proposed bridge has a 210% higher structural performance than the designed load under the lateral load. Abstract: This paper proposes a novel bridge construction method that affords increased constructability. In the proposed method, only some of the concrete members of the bridge are cast in place and then joined with precast concrete copings with internal connectors or precast concrete girders. This method enhances constructability by facilitating field assembly and minimizing the field casting work. Furthermore, in the case of a bridge exposed to ocean loads, the structural stability can be improved by integrating steel piers with the precast concrete copings. To analyze the connection behavior of a bridge constructed via the proposed method, a full-scale specimen with a span of 3.0 m was fabricated and tested under lateral loading. A finite element analysis model was also developed for theoretical analysis. The experimentally and theoretically determined lateral behaviors of the bridge during each loading step were compared. The final failure mode of the bridge yielded to the reinforcement in the joint between a precast coping and a cast-in-place member. Nevertheless, the proposed method was found to offer improved structural performance, increasing the maximum lateral load of the bridge to 210% of the design value.